2008
DOI: 10.1039/b803727b
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the performance of spin-component scaled CC2 in ground and electronically excited states

Abstract: A generalization of the spin-component scaling and scaled opposite-spin modifications of second-order Møller-Plesset perturbation theory to the approximate coupled-cluster singles-and-doubles model CC2 (termed SCS-CC2 and SOS-CC2) is discussed and a preliminary implementation of ground and excited state energies and analytic gradients is reported. The computational results for bond distances, harmonic frequencies, adiabatic and 0-0 excitation energies are compared with experimental results to benchmark their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
323
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(330 citation statements)
references
References 58 publications
4
323
1
2
Order By: Relevance
“…SCS-CC2 has been successfully used for ground and excited states of aromatic systems. 43,44 For comparison, the structures were also optimized using the PBE0 and B3LYP density functionals in conjunction with the D3 correction with Becke-Johnson damping (PBE-D3BJ, B3LYP-D3); the def2-TZVP basis set was used with PBE0-D3 and the TZVPP basis set with B3LYP-D3. [45][46][47][48][49][50] 12 different starting structures were generated and then optimized using the two DFT methods.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…SCS-CC2 has been successfully used for ground and excited states of aromatic systems. 43,44 For comparison, the structures were also optimized using the PBE0 and B3LYP density functionals in conjunction with the D3 correction with Becke-Johnson damping (PBE-D3BJ, B3LYP-D3); the def2-TZVP basis set was used with PBE0-D3 and the TZVPP basis set with B3LYP-D3. [45][46][47][48][49][50] 12 different starting structures were generated and then optimized using the two DFT methods.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…This scaling enhances the accuracy of 0-0 transition energies both for ππ * and nπ * states. 42 In a recent benchmark study, it was shown that the standard deviation of 0-0 transition energies for a set of organic molecules is 0.06 eV. 43 For the calculations of SCS-CC2 energies we used the standard scaling factors 1/3 for the same-spin and 6/5 for the opposite-spin components.…”
Section: A Computational Methodsmentioning
confidence: 99%
“…Accurate electron-correlation methods, such as high-order configuration interaction (CI) or coupledcluster (CC) schemes, yield excitation energies in close agreement with experiment when using large basis sets. [1][2][3][4][5] However, high-order CI and CC calculations are limited to very small molecules, 6 often comprising no more than a few tens of atoms, and therefore not applicable for studying a) Electronic mail: Robert.Send@kit.edu. b) Electronic mail: Ville.Kaila@nih.gov.…”
Section: Introductionmentioning
confidence: 99%